Two new species of Hydraena Kugelann, 1794 from Brazil (Coleoptera: Hydraenidae) - Benetti, Cesar J.; Valladares, Luis F.; Delgado, Juan A.; Hamada, Neusa (Zootaxa, 2020)
Hydraena (Hydraenopsis) josefinae sp. nov. and H. (H.) pernambucana sp. nov. are described respectively from Amapá and Pernambuco States, Brazil. Hydraena (H.) josefinae sp. nov. is a member of the scintillabella subgroup of the leechi group, while H. (H.) pernambucana sp. nov. belongs to the orcula complex in the marginicollis subgroup of the marginicollis group. Descriptions and diagnostic characters for both new species are offered; habitus photographs and line drawings of male genitalia of the two new species, as well as drawings of female genitalia of H. josefinae sp. n., are provided. Male genitalia of H. alterra Perkins, 1980 is illustrated and compared with that of the closely related H. josefinae sp. nov. Habitat and distributional data of the two new species are also included.